The Influence Of Brand Conformity, Consumer Value And Consumer Trust On Brand Loyalty Mediated By Customer Satisfaction - Rani Suryani; Dedi Suharyadi; Nurhadi Nurhadi; Bilgah Bilgah; Nurul Aisyah (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
This article investigates the complex interplay of brand conformity, consumer values, consumer trust, and customer satisfaction in shaping brand loyalty within the context of PT. Hexindo Adiperkasa, Tbk. Through a comprehensive analysis utilizing the Smart PLS technique, the study explores both direct and indirect relationships among these variables. The results reveal significant positive associations between brand conformity, consumer trust, and customer satisfaction with brand loyalty. Notably, brand conformity demonstrates a substantial direct influence on brand loyalty, emphasizing the importance of a consistent brand identity. Furthermore, the mediating role of customer satisfaction is evident, particularly in the relationships between consumer trust and brand loyalty, as well as brand conformity and brand loyalty. While the direct link between consumer values and brand loyalty is not statistically significant, the article underscores the need for further investigation into influencing factors. These findings offer strategic insights for PT. Hexindo Adiperkasa, emphasizing the significance of maintaining brand consistency, fostering consumer trust, and prioritizing customer satisfaction to cultivate and sustain brand loyalty in a competitive market.